2021
DOI: 10.1007/s00431-021-04035-w
|View full text |Cite
|
Sign up to set email alerts
|

Steroid treatment for the first episode of childhood nephrotic syndrome: comparison of the 8 and 12 weeks regimen using an individual patient data meta-analysis

Abstract: Steroids are the cornerstone of the treatment of childhood nephrotic syndrome. The optimal duration for the first episode remains a matter of debate. The aim of this study is to determine whether the 8 weeks International Study of Kidney Disease in Children (ISKDC) regimen is equally effective as the 12 weeks steroid regimen from the German society of pediatric nephrology (Arbeitsgemeinschaft für Pädiatrische Nephrologie [APN]). An individual patient data (IPD) meta-analysis of randomized controlled trials rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Following the first episode, 70%–90% of children with SSNS relapse 1 year after disease onset 12. Data from a meta-analysis6 demonstrated that the median time to relapse was 63 days after cessation of 12 weeks of corticosteroids. Relapse-free rates at 3, 6, 12 and 24 months after the end of continuous therapy were 71%, 44%, 29% and 23%, respectively 6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the first episode, 70%–90% of children with SSNS relapse 1 year after disease onset 12. Data from a meta-analysis6 demonstrated that the median time to relapse was 63 days after cessation of 12 weeks of corticosteroids. Relapse-free rates at 3, 6, 12 and 24 months after the end of continuous therapy were 71%, 44%, 29% and 23%, respectively 6.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a meta-analysis6 demonstrated that the median time to relapse was 63 days after cessation of 12 weeks of corticosteroids. Relapse-free rates at 3, 6, 12 and 24 months after the end of continuous therapy were 71%, 44%, 29% and 23%, respectively 6. The overall 1-year relapse rate of first-onset INS in our unpublished data from China was similar to the results of the previous meta-analysis 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, therapy for 2 months versus 3 months or longer was not associated with increased risk of relapse (RR 0.91; 95% CI 0.78-1.06; 637 participants; 5 studies; I 2 = 47%) or frequent relapses (RR 0.99; 95% CI 0.82-1.19; 585 participants, 4 studies; I 2 = 0%). Individual patient data analyses of two European studies suggest that initial therapy for 12 weeks was better than 8 weeks in terms of delaying the time to first relapse (63 vs. 29 days; log rank P = 0.04) and fewer relapses on short-term followup (1.2 vs. 0.8 relapses per year; relative relapse rate 0.66; 95% CI 0.49-0.90) [13]. Post hoc analyses of the Indian [9] and British [11] placebo-controlled RCTs indicated that prolonged therapy in young children might reduce the risk of first relapse, but not frequent relapses [9].…”
Section: Therapy For the First Episodementioning
confidence: 98%